CHIMBOTE IN DANGER: THE SILENT IMPACT OF POLLUTION AND THE POWER OF COMMUNITY ACTION. - Chávez Lozano, Paola Inés; Cholán Terán, Ximena; Rodríguez Castañeda, Yessenia Nathalí (LACCEI, 2024)
In this article, the research focuses mainly on evidencing the critical deficiency of green and recreational spaces in the districts of Chimbote and Nuevo Chimbote, which have high pollution rates. Likewise, the approach of environmental and eco-friendly proposals to solve or reduce pollution in the city, despite the fact that it presents scenarios where said pollution directly and drastically affects people and the natural environment. Nowadays, this problem is not addressed and nothing is done about it, in the district there is a significant shortage of green areas, squares, squares and parks, which are in poor condition or with high levels of contamination, in addition of the nonexistence of Community Centers and Community Centers focused on environmental issues; likewise, one of the biggest problems is the lack of concern and disinterest of the population and the authorities themselves.